Brain and Smartphone Addiction: A Systematic Review - C. Anbumalar; D. Binu Sahayam (Human Behavior and Emerging Technologies)
In recent years, the smartphone has become ubiquitous in everyone’s lives. The smartphone has both positive and negative impacts on the users. Although addiction has been extensively studied, not much has been done to examine the association between neurofunctional regional activation and problematic smartphone use. This review, therefore, is systematically aimed at understanding the different neurofunctional regional activation differences related to smartphone addiction. The systematic review was done in four stages as follows: (1) identifying the techniques/instruments used in the literature (database search), (2) identifying relevant literature, (3) identifying criteria for inclusion and exclusion, and (4) acquiring full-text papers. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to conduct the systematic review. The literature was searched using the following databases: PubMed, Science Direct, Taylor & Francis, and Springer Link. The inclusion requirements were met by 7 articles out of 28896. The study on smartphone addiction with a focus on neurofunctional regional activation is limited. This review sheds light on neurofunctional regional activation associated with problematic smartphone usage. This will open the door to focused interventions and well-informed approaches to digital well-being in our technologically advanced society.